A phase I/II trial of weekly nab‐paclitaxel for pretreated non‐small‐cell lung cancer patients without epidermal growth factor receptor mutations and anaplastic lymphoma kinase rearrangement. Issue 4 (1st April 2019) - Harada, Daijiro; Kozuki, Toshiyuki; Nogami, Naoyuki; Bessho, Akihiro; Hosokawa, Shinobu; Fukamatsu, Nobuaki; Hotta, Katsuyuki; Ohashi, Kadoaki; Kubo, Toshio; Yoshioka, Hiroshige; Yokoyama, Toshihide; Sone, Naoyuki; et al.
Abstract: Aim: We investigated the efficacy, safety and optimal schedule of nanoparticle albumin‐bound paclitaxel monotherapy as second‐ or third‐line treatment for non‐small‐cell lung cancer patients without epidermal growth factor receptor mutation and anaplastic lymphoma kinase rearrangement. Methods: Patients with pretreated advanced non‐small‐cell lung cancer without epidermal growth factor receptor mutation and anaplastic lymphoma kinase rearrangement were included. The patients were administered 100 mg/m 2 of nanoparticle albumin‐bound paclitaxel on days 1, 8, 15 and 22 (level 0) or on days 1, 8 and 15 (level –1) every 4 weeks during phase I of the trial. The primary endpoint was objective response rate. The estimated objective response rate was 15% and the threshold was 5% with an α error of 0.05 and β error of 0.2 in phase II. Results: The recommended schedule was determined as level –1 in phase I. The characteristics of the 55 patients enrolled in phase II were as follows: median age = 66 years, male/female = 40/15, second/third line = 34/21 and adenocarcinoma/squamous cell carcinoma/large cell carcinoma/others = 34/17/2/2. Objective response rate was 7.3% (95% confidence interval, 2.0–17.6%). Median progression‐free survival was 3.4 months. Treatment‐related grade 3 or 4 toxicities were neutropenia (36.4%), febrile neutropenia (5.5%) and pulmonary infection (3.6%). Three patients had grade 2 pneumonitis and one treatment‐related death occurred due to adult respiratory distress syndrome. Conclusion: This study failed to meet predefined primary endpoints for pretreated patients with advanced non‐small‐cell lung cancer without epidermal growth factor receptor mutation and anaplastic lymphoma kinase rearrangement.